Resuelve estas ecuaciones.
a) 2x + 21 = 3x − 6 d) 3x − 2 + 7x = 7 − 1
b) 12 (x − 2) = 1 − x e) 4 (2x + 3) − 2x = 4x + 20
c) x + 5x − 4 = 18 − 2x f) 34 = 3x − 6 + 2x
Resuelve:
a) 6 (7 − x) = 8 (6 − x) e) 4 (x − 6) = 12 − (x + 3)
b) −8 (10 − x) = −6 f) −2 (x + 3) − 4 = 18 + 4x
c) (x + 2) · 3 = (13 − x) · 4 + 3 g) 2 (3x + 1) − x + 6 = 2 (x − 1)
d) 3 (1 − 2x) + 12 = 10 − 2 (x − 3
jjhsjdmj:
esta bien facil y yo te voy a ayudar
Respuestas
Respuesta dada por:
34
a) x=27
b) x=1,9
c) x mas 5x menos 4=18 menos 2x
8x=22
b) x=1,9
c) x mas 5x menos 4=18 menos 2x
8x=22
Respuesta dada por:
195
a) 2x + 21 = 3x − 6
2 x - 3 x = - 6 - 21
- x = - 27
x = 27
d) 3x − 2 + 7x = 7 − 1
10 x = 7 - 1 +2
10 x = 8
x = 8/10
x = 4/5
b) 12 (x − 2) = 1 − x
12 x - 24 = 1 - x
12 x + x = 1 + 24
13 x = 25
x = 25/13
e) 4 (2x + 3) − 2x = 4x + 20
8 x + 12 - 2 x = 4 x + 20
8 x - 2 x - 4 x = 20 - 12
2 x = 8
x = 8/2
x = 4
c) x + 5x − 4 = 18 − 2x
x + 5 x + 2 x = 18 + 4
8 x = 22
x = 22/8
x = 11/4
f) 34 = 3x − 6 + 2x
34 + 6 = 5 x
40= 5 x
40/5 = x
8 = x
Resuelve:
a) 6 (7 − x) = 8 (6 − x)
42 - 6 x = 48 - 8 x
42 - 48 = - 8 x + 6 x
- 6 = - 2 x
- 6 / -2 = x
3 = x
e) 4 (x − 6) = 12 − (x + 3)
4 x - 24 = 12 - x - 3
4 x + x = 12 + 24 - 3
5 x = 33
x = 33/5
b) −8 (10 − x) = −6
- 80 + 8 x = - 6
8 x = - 6 + 80
8 x = 74
x = 74/8
x = 37/4
f) −2 (x + 3) − 4 = 18 + 4x
- 2 x - 6 - 4 = 18 + 4 x
- 2 x - 4 x = 18 + 6 + 4
- 6 x =28
x = - 28 / 6
c) (x + 2) · 3 = (13 − x) · 4 + 3
3 x + 6 = 52 x - 4 x + 3
3 x - 52 x + 4 x = 3 - 6
45 x = - 3
x = - 3/45
g) 2 (3x + 1) − x + 6 = 2 (x − 1)
6 x + 2 - x + 6 = 2 x - 2
6 x - x - 2 x = - 2 - 2 - 6
3 x = - 10
x = - 10/3
d) 3 (1 − 2x) + 12 = 10 − 2 (x − 3
3 - 6 x + 12 = 10 - 2 x + 6
- 6 x + 2 x = 10 + 6 - 3 - 12
4 x = 1
x = 1/5
2 x - 3 x = - 6 - 21
- x = - 27
x = 27
d) 3x − 2 + 7x = 7 − 1
10 x = 7 - 1 +2
10 x = 8
x = 8/10
x = 4/5
b) 12 (x − 2) = 1 − x
12 x - 24 = 1 - x
12 x + x = 1 + 24
13 x = 25
x = 25/13
e) 4 (2x + 3) − 2x = 4x + 20
8 x + 12 - 2 x = 4 x + 20
8 x - 2 x - 4 x = 20 - 12
2 x = 8
x = 8/2
x = 4
c) x + 5x − 4 = 18 − 2x
x + 5 x + 2 x = 18 + 4
8 x = 22
x = 22/8
x = 11/4
f) 34 = 3x − 6 + 2x
34 + 6 = 5 x
40= 5 x
40/5 = x
8 = x
Resuelve:
a) 6 (7 − x) = 8 (6 − x)
42 - 6 x = 48 - 8 x
42 - 48 = - 8 x + 6 x
- 6 = - 2 x
- 6 / -2 = x
3 = x
e) 4 (x − 6) = 12 − (x + 3)
4 x - 24 = 12 - x - 3
4 x + x = 12 + 24 - 3
5 x = 33
x = 33/5
b) −8 (10 − x) = −6
- 80 + 8 x = - 6
8 x = - 6 + 80
8 x = 74
x = 74/8
x = 37/4
f) −2 (x + 3) − 4 = 18 + 4x
- 2 x - 6 - 4 = 18 + 4 x
- 2 x - 4 x = 18 + 6 + 4
- 6 x =28
x = - 28 / 6
c) (x + 2) · 3 = (13 − x) · 4 + 3
3 x + 6 = 52 x - 4 x + 3
3 x - 52 x + 4 x = 3 - 6
45 x = - 3
x = - 3/45
g) 2 (3x + 1) − x + 6 = 2 (x − 1)
6 x + 2 - x + 6 = 2 x - 2
6 x - x - 2 x = - 2 - 2 - 6
3 x = - 10
x = - 10/3
d) 3 (1 − 2x) + 12 = 10 − 2 (x − 3
3 - 6 x + 12 = 10 - 2 x + 6
- 6 x + 2 x = 10 + 6 - 3 - 12
4 x = 1
x = 1/5
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años